Speak or shout? Nonverbal vocalizations promote rapid detection of emotions in vocal communication - Marc D. Pell; Haining Cui; Yondu Mori; Xiaoming Jiang (PLoS ONE, 2026)
Human vocal expressions of emotion can be expressed nonverbally, through vocalizations such as shouts or laughter, or speakers can embed emotional meanings in language by modifying their tone of voice (“prosody”). Is there evidence that nonverbal expressions promote “better” (i.e., more accurate, faster) recognition of emotions than speech, and what is the impact of language experience? Our study investigated these questions using a cross-cultural gating paradigm, in which Chinese and Arab listeners (n = 25/group) judged the emotion communicated by acoustic events that varied in duration (200 milliseconds to the full expression) and form (vocalizations or prosody expressed in listeners’ native, second or foreign language). Accuracy was higher for vocalizations overall, but listeners were markedly more efficient to form stable categorical representations of the speaker’s emotion from vocalizations (M = 417ms) than native prosody (M = 765ms). Language experience enhanced recognition of emotional prosody expressed by native/ingroup speakers for some listeners (Chinese) but not all (Arab), emphasizing the dynamic interplay of socio-cultural factors and stimulus quality on prosody recognition which occurs over a more sustained time window. Our data show that vocalizations are functionally suited to build robust, rapid impressions of a speaker’s emotion state unconstrained by the listener’s linguistic cultural background.